ASUHAN KEPERAWATAN PASIEN YANG MENGALAMI INFARK MIOKARD AKUT DENGAN NYERI MELALUI TEKNIK RELAKSASI NAFAS DALAM - Wiwik Sofiah; Laely Febriani Roswah (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2022)
Acute myocardial infarction (AMI), also known as cardiac arrest, is a life-threatening condition, characterized by the formation of localized necrotic areas within the myocardium. Symptoms of AMI are chest pain like being hit by a heavy object, which can occur while doing activities or resting. This condition must be treated immediately to mrevent further complications. The purpose of this case study is to provide an overview of the implementation of nursing care for patients who experience acute myocardial infarction with pain through deep breathing relaxation techniques. This research method uses a case study by collecting data from 3 (three) respondents. The case study was conducted at the Koja Hospital, North Jakarta in June 2019. The assessment was carried out using the Doengoes pattern, followed by the determination of nursing diagnoses referring to the NANDA Nursing. Diagnosis. For planning and implementation using NIC Interventions. Meanwhile, at the evaluation stage, it refers to NOC outcomes. The three respondents took action to reduce pain with deep breathing relaxation techniques. This technique was carried out for 3 meetings with a duration of 10 minutes each. The results obtained are a reduction in pain and a decrease in pain scale in all respondents. It can be concluded that deep breathing relaxation techniques are very helpful in reducing pain, although the main action to reduce pain is pharmacological action.